Saliva: Physiology and Diagnostic Potential in Health and Disease - Sebastien J. C. Farnaud; Ourania Kosti; Stephen J. Getting; Derek Renshaw (The Scientific World Journal)
Saliva has been described as the mirror of the body. In a world of soaring healthcare costs and an environment where rapid diagnosis may be critical to a positive patient outcome, saliva is emerging as a viable alternative to blood sampling. In this review, we discuss the composition and various physiological roles of saliva in the oral cavity, including soft tissue protection, antimicrobial activities, and oral tissue repair. We then explore saliva as a diagnostic marker of local oral disease and focus particularly on oral cancers. The cancer theme continues when we focus on systemic disease diagnosis from salivary biomarkers. Communicable disease is the focus of the next section where we review the literature relating to the direct and indirect detection of pathogenic infections from human saliva. Finally, we discuss hormones involved in appetite regulation and whether saliva is a viable alternative to blood in order to monitor hormones that are involved in satiety.